VSA-3000: A Quantitative Vibration Sensation Testing Device for Patients With Central Nervous System Injury - Gao, Mingming; Yun, Xiaoping; Zhang, Tong (Frontiers in Neurology, 2020)
Vibration Sensory Analyzer-3000 (VSA-3000) has been shown a good method of assessing vibration sense of peripheral neuropathy, however, few studies have investigated a relationship between quantitative vibration perception threshold (VPT) and central nervous system (CNS) disorders. In this prospective clinical trial performed in the China Rehabilitation Research Center, we analyzed the diagnostic accuracy of the VSA-3000 in evaluating VPT, in patients with CNS injury (stroke and spinal cord injuries (SCI)), against the reference standard of Somatosensory evoked potential (SSEP) measurements, and to assess whether the VSA-3000 device offers superior accuracy compared with other routine test (e.g. the tuning fork) for impaired vibration sensation caused by CNS diseases. Sixty patients (30 stroke and 30 spinal cord injury) were recruited. The results showed that the ICC for VPTs was in the “substantial” range and the kappa value between VSA-3000 and SSEP was 0.877, which was higher than that of tuning fork (0.732). The VSA-3000 had good diagnostic accuracy with a sensitivity of 94.8%, specificity of 92.9%, and positive-predictive value of 93.8% and negative-predictive value of 94.0%, each value was higher than that of tuning fork. The area under the receiver operating characteristic curve (AUC) of VSA-3000 was 0.95 and that of tuning fork was 0.89, and there was a significant difference between the two values (P=0.0216). The types of injury and age were the independent correlates of the VPTs.